Technology-Enabled Innovation for Democracy, Government and Governance Second Joint International Conference on Electronic Government and the Information Systems Perspective, and Electronic Democracy, EGOVIS/EDEM 2013, Prague, Czech Republic, August 26-28, 2013, Proceedings - KQ, Andrea.; Leitner, Christine.; Leitold, Herbert.; Prosser, Alexander. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the Second Joint International Conference on Electronic Government and the Information Systems Perspective, and Electronic Democracy, EGOVIS/EDEM 2013, held in Prague, Czech Republic, in August 2013, in conjunction with DEXA 2013. The 19 revised full papers presented were carefully reviewed and selected for inclusion in this volume. They focus on the currently most sensitive areas in the field, such as identity management as a core component in any e-government or participation system, open data, mobile government applications as well as intelligent and learning systems.The papers are organized in the following topical sections: identity management in e-government; intelligent systems in e-government; e-government cases; mobile government; open government data; and e-participation.